TINJAUAN TERHADAP PERAN PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PERLINDUNGAN BAGI PENERIMA HIBAH TERHADAP OBJEK HIBAH BAGI AHLI WARIS PEMBERI HIBAH (STUDI KASUS PUTUSAN PENGADILAN NEGERI LARANTUKA NOMOR 7/PDT.G/2016/PN.LRT TANGGAL 15 MEI 2017) - Chelvia Priscilla; Gunawan Djajaputra (Jurnal Hukum Adigama, 2020)
In the use of ownership rights over land and buildings, one of the most common can be done is transitional. The transfer referred to is the transfer of rights between one party to another party, one of which is a grant. The role of PPAT is very important in protecting the legal certainty of the implementation of a grant, especially in protecting the will of the grantee to provide the grant object and the grantee who receives the object of the grant from a lawsuit that may occur in the future by the beneficiary of the grant, where a person who has passed away is not can again give the explanation. In everyday life it is not uncommon to find in a family, the transfer of assets of parents who are not known to their children as experienced by the family of the late Clara Diaz in the Verdict of the Larantuka District Court Number 7 / Pdt.G / 2016 / PN.Lrt Date May 15, 2017 which resulted in a lawsuit at a later date. So that a PPAT deed has a big role to be an authentic proof and protector of the will of the parties in making a grant.